Grundrechte für Tiere Eine Kritik des geltenden Tierschutzrechts und rechtstheoretische Grundlegung von Tierrechten im Rahmen einer Neupositionierung des Tieres als Rechtssubjekt - Stucki, Saskia (Fundamenta Juridica. Beiträge zur rechtswissenschaftlichen Grundlagenforschung, 2016)
"This book concerns itself with the contemporary question of animal rights - an issue hitherto understudied by legal scholars. Against the backdrop of the merits and shortcomings of current animal welfare law, it provides an in-depth exploration of the idea of animal rights from a legal theoretical perspective. On the basis of a critical appraisal of the existing legislative regime governing animal welfare, the author proposes a paradigm change towards a rights-based framework for legal animal protection. The study examines such a reconception of animals' legal status as legal subjects and holders of (fundamental) rights by means of analysis of the relevant legal concepts - legal personhood, rights, and human rights - with regard to their applicability to animals. This study is marked by its distinctly legal theoretical approach to the subject of animal rights, and addresses scholars of all disciplines with an interest in animal welfare as well as in the foundations of law."